Taman Kanak-Kanak sebagai Pondasi dalam Menanamkan Nilai-Nilai Toleransi - ismail, Ismail (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
Kindergarten is an educational institution that is held before the basic education level. The purpose of this study is to describe the values ​​of tolerance applied in kindergartens in North Sumatra. This research method uses descriptive qualitative research. The data collection of this research are interviews, observations, and literature studies. The results of this study indicate that in kindergarten there are no subjects about tolerance. The form of tolerance in kindergarten is in the form of speech/expression, and examples practiced by the teacher. All forms of tolerance contain the values ​​of tolerance, namely respecting the cultural differences of each tribe, considering all people as equal, respecting the cultural differences of each ethnic group, acknowledging other beliefs and religions, respecting everyone's opinions, and assuming all people are equal, ethics and manners, working together and help each other, respect and recognize other religious beliefs Keywords: Kindergarten, Tolerance Value